Mechanical transmission of African swine fever virus by Stomoxys calcitrans: Insights from a mechanistic model. Issue 3 (24th September 2020) - Vergne, Timothée; Andraud, Mathieu; Bonnet, Sarah; De Regge, Nick; Desquesnes, Marc; Fite, Johanna; Etore, Florence; Garigliany, Mutien‐Marie; Jori, Ferran; Lempereur, Laetitia; Le Potier, Marie‐Frédérique; Quillery, Elsa; et al.
Abstract: African swine fever (ASF) represents a global threat with huge economic consequences for the swine industry. Even though direct contact is likely to be the main transmission route from infected to susceptible hosts, recent epidemiological investigations have raised questions regarding the role of haematophagous arthropods, in particular the stable fly ( Stomoxys calcitrans ). In this study, we developed a mechanistic vector‐borne transmission model for ASF virus (ASFV) within an outdoor domestic pig farm in order to assess the relative contribution of stable flies to the spread of the virus. The model was fitted to the ecology of the vector, its blood‐feeding behaviour and pig‐to‐pig transmission dynamic. Model outputs suggested that in a context of low abundance (<5 flies per pig), stable flies would play a minor role in the spread of ASFV, as they are expected to be responsible for around 10% of transmission events. However, with abundances of 20 and 50 stable flies per pig, the vector‐borne transmission would likely be responsible for almost 30% and 50% of transmission events, respectively. In these situations, time to reach a pig mortality of 10% would be reduced by around 26% and 40%, respectively. The sensitivity analysis emphasized that the expected relative contribution of stable flies was strongly dependent on the volume of blood they regurgitated and the infectious dose for pigs. This study identified crucial knowledge gaps that need to be filled in order to assess more precisely the potential contribution of stable flies to the spread of ASFV, including a quantitative description of the populations of haematophagous arthropods that could be found in pig farms, a better understanding of blood‐feeding behaviours of stable flies and the quantification of the probability that stable flies partially fed with infectious blood transmit the virus to a susceptible pig during a subsequent blood‐feeding attempt.